2018
DOI: 10.1029/2018jd029247
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Synoptic and Local Factors on Heat Wave Events Over Southeastern Region of Korea in 2015

Abstract: Because of global warming and abnormal climate change, record-breaking heat wave events have been increasing. Therefore, it is necessary to analyze and predict the mechanisms for generating and developing heat waves. In this study, the impacts of synoptic and local factors on heat waves over the southeastern region of South Korea in 2015 are investigated. First, Heat wave events for 1980-2016 defined by spatiotemporal criteria are classified into three clusters using the K-means clustering analysis. Heat wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 39 publications
0
45
0
3
Order By: Relevance
“…The possible mechanisms behind extreme heatwaves in Korea are complex and have not been fully explored (Kim et al 2019). However, the extent and strength of the western North Pacific subtropical high around Korea are often investigated to explain the physical mechanism that is responsible for the heatwaves in South Korea (Yeh et al 2018, Yoon et al 2018. This is because extreme heatwaves are linked to a specific atmospheric circulation at the synoptic scale (Lee and Lee 2016), even though they are a locally dominating phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms behind extreme heatwaves in Korea are complex and have not been fully explored (Kim et al 2019). However, the extent and strength of the western North Pacific subtropical high around Korea are often investigated to explain the physical mechanism that is responsible for the heatwaves in South Korea (Yeh et al 2018, Yoon et al 2018. This is because extreme heatwaves are linked to a specific atmospheric circulation at the synoptic scale (Lee and Lee 2016), even though they are a locally dominating phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Busan experienced an average of 13.2 TNs, which is much greater than 3.4 HW days. These results were consistent with previous research, which indicated that TNs were affected more by urban heat island effect than the air temperature based on city location (Yoon et al ., ). However, the focus of this study is on HW events and TNs were considered only to identify extreme conditions.…”
Section: Resultsmentioning
confidence: 97%
“…한반도에 발생하는 폭염에 대한 연구는 주로 사례를 분석 하는 경우가 주를 이루고 있다 (Back et al, 2018;Yoon et al, 2018). 폭염을 유발하는 원인은 발생지역에 따라 다르지만 주로 북태평양 고기압의 발달과 연관성이 높다.…”
Section: 서 론unclassified
“…폭염을 유발하는 원인은 발생지역에 따라 다르지만 주로 북태평양 고기압의 발달과 연관성이 높다. Yoon et al (2018) (Kim and Kim, 2013), 양간지풍은 한반도를 중심으로 기압이 남고북저의 형태로 배치되었을 때 서풍이 태백산맥을 넘으 면서 고온건조한 대기가 영동지역으로 형성된다 (Jang and Chun, 2008;Cho et al, 2015).…”
Section: 서 론unclassified
See 1 more Smart Citation